ABOUT SOME UNKNOWN ASPECTS OF IONA KHELASHVILI’S (1778-1837) LIFE AND WORK - Metropolitan of Poti; Khobi Grigol (Berbichashvili) (European Scientific Journal, ESJ, 2014)
Great Georgian philosopher and theologian Iona Khelashvili (1778-1837) lived andworked in the period and epoch marked by very dramatic events for Georgia. Importantaspects of the biography of this Georgian thinker have not been studied yet. The aim of thefollowing article is to study and make as a subject of special discussion those stages andepisodes of life of Iona Khelashvili which are unknown or need specification and furtherresearch. For this purpose, the author of the paper studied historical materials and documentskept in the Central State Historical Archive of Saint Petersburg that were unknown forresearchers of Georgian philosophical thought so far. Based on the unknown materials anddocuments, the author revealed many important details, episodes and moments from IonaKhelashvili’s life and work (one of the important findings is the establishment of the date ofhis birth).